Cardiovascular Disease in HIV Infection - Sánchez-Torres, Reinaldo J.; García-Palmieri, Mario R. (Puerto Rico Health Sciences Journal, 2009)
Cardiovascular disease has been well documented in patients with Human Immunodeficiency Virus infection, especially after the introduction of highly active antiretroviral therapy. At present, HIV infection is one of the leading causes of acquired cardiovascular disease including heart failure. Some of the changes observed in these patients include left ventricular systolic dysfunction, dilated cardiomyopathy, congestive heart failure, myocarditis, lipodystrophy, dyslipidemia, insulin resistance, accelerated atherosclerosis including myocardial infarction, prothrombotic state, pericardial effusion, pulmonary hypertension, autonomic dysfunction, and malignancy. This article summarizes the main findings in the principal HIV-associated cardiovascular manifestations in order to stimulate its early recognition so helping in early intervention and therapy.